2012
DOI: 10.1186/1471-2458-12-796
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of how young adults perceive tobacco brands: implications for FCTC signatories

Abstract: BackgroundThe Framework Convention on Tobacco Control calls for the elimination of tobacco advertising, promotion and sponsorship. To test whether tobacco packaging functions as advertising by communicating attractive and distinctive brand attributes, we explored how young adult smokers and non-smokers interpreted familiar and unfamiliar tobacco brands.MethodsWe conducted an on-line survey of 1035 young adult smokers and non-smokers aged 18–30. Participants evaluated eight tobacco brands using ten attributes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…Corporate branding on the packaging appeared to diminish perceptions of harm and increase positive perceptions of product quality compared to products in plain packaging. These findings are consistent with what other studies on combustible tobacco products have shown with regard to the influence of product packaging on consumer perceptions of the product [14,17,20,21,31]. In December 2012 plain packaging legislation was passed in Australia with the intent to reduce the appeal of packaging to consumers and increase the noticeability and salience of health warnings, among others (see Tobacco Plain Packaging Act 2011 for more detail: http://www.comlaw.gov.au/Details/C2011A00148).…”
Section: Discussionsupporting
confidence: 92%
“…Corporate branding on the packaging appeared to diminish perceptions of harm and increase positive perceptions of product quality compared to products in plain packaging. These findings are consistent with what other studies on combustible tobacco products have shown with regard to the influence of product packaging on consumer perceptions of the product [14,17,20,21,31]. In December 2012 plain packaging legislation was passed in Australia with the intent to reduce the appeal of packaging to consumers and increase the noticeability and salience of health warnings, among others (see Tobacco Plain Packaging Act 2011 for more detail: http://www.comlaw.gov.au/Details/C2011A00148).…”
Section: Discussionsupporting
confidence: 92%
“…These metaphors seem intuitively likely to appeal to women with less education who occupy lower socioeconomic positions, and who preferred this compound descriptor to options featuring only their existing brand descriptor, ‘Red’. This interpretation reflects findings from earlier qualitative studies, which explicated the important symbolic qualities brands confer on smokers,5 and is consistent with our wider understanding of tobacco branding, which smokers use to access identities that offer a more appealing reality 4 6 22…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the shortage of significant differences between conditions among males could be the result of a very high degree of awareness of the differences between brand images, so that the brand associations stay on after only the brand name remains to identify the product. Previous research has concluded both in favour24 and against25 the significance of gender on perceptions of pack design and plain packaging.…”
Section: Discussionmentioning
confidence: 99%